Research of Pontoon Bridge Elements in View of Modern Challenges in Terms of Load Capacity - Perepelytsia, K. M.; Kliuchnyk, S. V. (Science and Transport Progress, 2025)
Purpose. The main purpose of this work is to study the current requirements for floating means for overcoming water obstacles; adaptation of the normative tracked load to the standard of dynamic effects of tracked and wheeled military loads of NATO countries; modeling of the elements of the pontoon bridge NZhM-56 using software to study it under the influence of modern load; study of the stress-strain state of the bridge elements to determine its carrying capacity. Methodology. The paper analyzes the current load capacity requirements for pontoon systems, taking into account the challenges of today, using the experience of NATO countries in the military classification of the load capacity of artificial structures. The internal forces in the elements of a pontoon bridge under the influence of a modern moving load are determined by the method of lines of influence. Software that implements the finite element method was used to study the pontoon bridge. Findings. The requirements of the modern NATO standard for military loads were investigated. An adaptive recalculation of the tracked load model, for which the structure was designed, was carried out to meet the NATO military load standard. The results of internal forces in the beams of the bridge span structure were obtained. Originality. The elements of the model of a pontoon bridge used to overcome water obstacles during the repulsion of the armed aggression of the Russian Federation were reproduced using software that allows to study the operation of the pontoon system (available resource) and to establish the real load capacity of the bridge, taking into account the requirements of the NATO standard for loading. The domestic tracked load was adapted to the requirements of NATO countries according to the classification of military vehicles. Practical value. Determination of the load capacity of pontoon bridge elements will allow rational use of the available resource, passage of modern loads in accordance with the challenges of today, as well as optimization and modernization of bridge structures. Determining the compliance of the domestic load classification with the requirements of NATO countries helps to ensure the passage of existing equipment through artificial structures classified according to modern standards.